Determination of Aflatoxins in Spices and Dried Fruits - Zahra, N.; Khan, M.; Mehmood, Z.; Saeed, M. K.; Kalim, I.; Ahmad, I.; Malik, K. A. (Journal of Scientific Research, 2018)
The purpose of current study was to estimate the incidence of total aflatoxins (B1+B2+G1+G2) in unpack spices and dried fruits. A total of 90 samples included red chillies, black pepper, figs and dried apricots were picked from shops/markets situated in Lahore - Pakistan and were analyzed by using thin layer chromatography (TLC). The results showed that aflatoxin B1 was detected in 24 (26%) samples. The results obtained were ranging between 23.99-97.42 μgkg-1 in spices, 47.68-75.78 μgkg-1 in black pepper, 6.72-14.43 μgkg-1 in figs while 13.2 μgkg-1 of aflatoxin B1 was present in apricot sample. 39.28%, 18.18%, 5.0% and 40% samples of red chilli, black pepper, dried apricots and figs were found contaminated with aflatoxins respectively. Among contaminated samples 32.14% , 13.63%, 5.0% and 15% samples of red chilli, black pepper, dried apricots and figs, respectively were found contaminated with aflatoxins beyond permissible limits. Furthermore, 17.77% i.e. n=16 of the positive samples contained Aflatoxin B1 level more than the permitted limit for entire aflatoxins as lay down by regulatory authority. From the study, it was concluded that a continuous and strict national monitoring plan is needed to improve quality and safety of spices and dried fruits supply in Pakistan.